Return Saham Pada Perusahaan Perbankan Di Indonesia - Sunarwijaya, I Ketut; Ernawatiningsih, Ni Putu Lisa; Dwiastari, Gek Ayu Sindy (Perspektif Akuntansi, 2024)
A stock return is the result or rate of return of a stock or investment. Expressed as a fixed percentage. If the company issuing the stock is healthy, the stock price will tend to perform better and the return received will increase. Analysis is performed using factors of profitability, solvency, liquidity, operating cash flow, and company size to examine which factors influence stock returns. The purpose of this study is to review the impact of profitability, solvency, liquidity, operating cash flow and company size. Equity returns of banking companies listed on the Indonesian Stock Exchange for the period 2019-2021. The data collection methods used in this study are library research and documentation. The method used to determine the sample for this study is targeted sampling. The sample size for this study was 29 samples, for a total sample size of 87. The data analysis technique used was multiple regression analysis. The results of this study show that liquidity and firm size have a positive impact on stock returns. Solvency has a negative impact on equity returns. Although profitable, operating cash flow does not affect shareholder returns.